التكييف الفقهي والقانوني للهدايا المقدمة لأصحاب المناصب العامة بين المشروعية والتحريم دراسة فقهية قانونية مقارنة (Comprehensive Journal of Science, 2026)
This study examines the juristic and legal characterization of gifts offered to public officials، It shows that gifts are originally permissible as a means of goodwill, but become illicit (ghulūl) or bribery when linked to office, intended to influence decisions, or used to secure benefits، The research outlines key juristic criteria for distinguishing lawful from unlawful gifts—such as the motive for giving, prior custom, suspicion of undue influence, and the presence of disputes—then compares these with modern criminal regulations, particularly Libyan legislation and anti-corruption law، It concludes with a unifying standard: the "functional/official nexus" as the decisive criterion for prohibition and criminalization.
Keywords: gift, bribery, gifts to officials, public office, juristic characterization, legal characterization, anti-corruption, Libyan legislation